Chemoprotective activity of the isoflavones, genistein and daidzein on mutagenicity induced by direct and indirect mutagens in cultured HTC cells - Lepri, Sandra Regina; Luiz, Rodrigo Cabral; Zanelatto, Leonardo Campos; Da Silva, Patrícia Benites Gonçalves; Sartori, Daniele; Ribeiro, Lucia Regina [UNESP]; Mantovani, Mario Sergio (Springer Nature, 2013)
Isoflavones are phenolic compounds widely distributed in plants and found in a high percentage in soybeans. They have important biological properties and are regarded as potential chemopreventive agents. The aim of this study was to verify the preventive effect of two soy isoflavones (genistein and daidzein) by a micronucleus assay, analysis of GST activity, and real-time RT-PCR analysis of GSTa2 gene expression. Mutagens of direct (doxorubicin) and indirect (2-aminoanthracene) DNA damage were used. Hepatoma cells (HTC) were treated with genistein or daidzein for 26 h at noncytotoxic concentrations; 10 μM when alone, and 0.1, 1.0 and 10 μM when combined with genotoxic agents. The micronucleus test demonstrated that both isoflavones alone had no genotoxic effect. Genistein showed antimutagenic effects at 10 μM with both direct and indirect DNA damage agents. On phase II enzyme regulation, the current study indicated an increase in total cytoplasmic GST activity in response to genistein and daidzein at 10 μM supplementation. However, the mRNA levels of GSTa2 isozymes were not differentially modulated by genistein or daidzein. The results point to an in vitro antimutagenic activity of genistein against direct and indirect DNA damage-induced mutagenicity. © 2012 Springer Science+Business Media B.V.
Keywords: Antimutagenicity; Daidzein; Genistein; Hepatoma cell line; Phase II enzyme; 2 aminoanthracene; daidzein; DNA; doxorubicin; genistein; glutathione transferase; glutathione transferase A2; isoflavone; mutagenic agent; antineoplastic activity; cell culture; chemoprophylaxis; cytotoxicity; DNA damage; enzyme activity; enzyme regulation; genotoxicity; hepatoma cell; mutagen testing; mutagenicity; nucleotide sequence; real time polymerase chain reaction; Glycine max